جودة البحث العلمي لدى هيئة التدريس بالجامعات الجزائرية وفقا للدليل الوطني الجديد للجودة الداخلية في التعليم العالي-دراستطبيقية لجامعة أدرار - Haouari, Mansour; Bendine, Amhamed (Finance and Business Economies Review, 2018)
The study aims at identifying the current situation of adopting the quality standards of scientific research which are outlined in the new national guide for internal quality formulated by the Ministry of Higher Education and Scientific Research in Algerian universities. The study approached this issue from the point of view of the teaching staff. In order to achieve the objectives of the study, a questionnaire was administered to some faculty members at the University of Adrar while ensuring that all five faculties are represented. The goal was to survey their views on the availability of quality requirements for scientific research. The statistical package for social sciences (SPSS) was used to analyze the questionnaire data and test the hypotheses. Based on the views of the surveyed participants, the study found that there is a poor implementation of the quality assurance requirements of the scientific research - as stated in the new quality manual - in the Algerian universities. The study recommends raising awareness of the importance of the quality of scientific research to improve the ranking of Algerian universities, developing effective mechanisms to improve scientific research, especially in terms of organization and structure, as well as building scientific partnerships for the sake of appreciating the value of scientific research.